Quality and Characteristics of 4241 Case Reports of Lactic Acidosis in Metformin Users Reported to a Large Pharmacovigilance Database - Brand KMG; Schlachter J; Foch C; Boutmy E (Dove Medical Press, 2022)
Kerstin MG Brand,1 Judith Schlachter,2 Caroline Foch,3 Emmanuelle Boutmy4 1Global Medical Affairs, Merck Healthcare KGaA, Darmstadt, Germany; 2Global Patient Safety, Merck Healthcare KGaA, Darmstadt, Germany; 3Global Epidemiology, Merck Healthcare KGaA, Darmstadt, Germany; 4Global Biostatistics, Merck Healthcare KGaA, Darmstadt, GermanyCorrespondence: Kerstin MG Brand, Global Medical Affairs, Merck Healthcare KGaA, F135/00_N1, Frankfurter Str. 250, Darmstadt, 64293, Germany, Tel +49 6151 72 2301, Email kerstin.brand@merckgroup.comObjective: Metformin-associated lactic acidosis (MaLA) occurs rarely and is thus difficult to study. We analysed 4241 individual case safety reports of lactic acidosis (LA) that implicated metformin as a suspected drug reported to the pharmacovigilance database of Merck KGaA, Darmstadt, Germany. The primary objective was to review reports for quality and completeness of data to support diagnoses of MaLA. We also explored the correlations between reported biomarkers, and associations between biomarkers and outcomes.Research Design and Methods: Records were analysed for completeness in supporting diagnoses of LA or metformin-associated LA (MaLA), against commonly used diagnostic criteria. Correlations between indices of exposure to metformin and biomarkers of LA and mortality were investigated.Results: Missing data was common, especially for plasma metformin. Clinical/biomarker evidence supported a diagnosis of LA in only 33% of cases (LA subpopulation) and of MaLA in only 9% (MaLA subpopulation). The metformin plasma level correlated weakly with plasma lactate (positive) and pH (negative). About one-fifth (21.9%) of cases reported a fatal outcome. Metformin exposure (plasma level or dose) was not associated with increased mortality risk (there was a suggestion of decreased risk at higher levels of exposure to metformin). Plasma lactate was the only variable associated with increased risk of mortality. Examination of concomitant risk factors for MaLA identified renal dysfunction (including of iatrogenic origin) as a potential driver of mortality in this population.Conclusion: Despite the high frequency of missing data, this is the largest analysis of cases of MaLA supported by measurements of circulating metformin, and lactate, and pH, to date. Plasma lactate, and not metformin dose or plasma level, appeared to be the main driver of mortality in the setting of LA or MaLA. Further research with more complete case reports is required.Keywords: lactic acidosis, metformin, type 2 diabetes, pharmacovigilance